Optoelectronic characteristics of CuO nanorods - 谢德华 王菲菲 吕浩 杜敏永 徐文杰 (Chinese physics B, 2013)
Optoelectronic characteristics of p-type CuO nanorods, synthesized by a simple hydrothermal method, were investi- gated at different atmospheres and oxygen pressures. The CuO nanorods have lower resistance in air than in a vacuum, unlike the n-type semiconductors. This is explained in terms of the surface accumulation conduction. Measurements at different oxygen pressures indicate that oxygen has an important effect on the optoelectronic properties of p-type nanoma- terials.